Battery packaging materials, molded cases, and battery cases

By using a base material protective layer of resin with high glass transition temperature and lubricant in the packaging material for batteries, the problem of poor sealing during the battery heat sealing process is solved, high heat resistance and good molding are achieved, and the sealing effect and capacity of the battery are improved.

CN222698067UActive Publication Date: 2025-04-01LISSENOK PACKAGING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202323411396.2
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Priority Date
2022-12-20
Filing Date
2023-12-14
Publication Date
2025-04-01
Estimated Expiration
2033-12-14

AI Technical Summary

Technical Problem

During the battery production process, the high temperature and high pressure heat sealing process leads to the precipitation of molecules in the polyamide resin layer and adheres to the sealing strips, causing the problem of poor sealing.

Method used

A substrate protective layer consisting of a resin with a glass transition temperature of 220°C or above and a lubricant is used to combine a polyamide imide resin without a curing agent and a specific lubricant to form a packaging material for a battery with high heat resistance and good moldability.

Benefits of technology

Effectively prevent the packaging materials for batteries from adhering to the sealing strips during the high-temperature heat sealing process, maintain a good sealing effect, and improve moldability and battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222698067U_ABST
    Figure CN222698067U_ABST
Patent Text Reader

Abstract

The utility model relates to a battery packaging material, a molded shell and a battery shell. The problem is to provide a battery packaging material that maintains good moldability and can prevent poor sealing caused by adhesion to a sealing strip even when heat-sealed at high temperatures. The solution is as follows: a battery packaging material (1) that includes at least a substrate protective layer (20), a substrate layer (13), a barrier layer (11), and a heat-fusible resin layer (15) in order from the outside to the inside, wherein the substrate protective layer (20) is composed of a resin composition containing a resin with a glass transition temperature of 220°C or more and a lubricant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to a battery packaging material used as a shell material for batteries, capacitors used in portable devices such as smart phones and tablets, and batteries, capacitors and other power storage devices used in hybrid vehicles, electric vehicles, wind power generation, solar power generation, and night power storage, and related technologies. Background Art

[0002] As the battery packaging material, a laminated packaging material in which resin films are laminated on both sides of a metal foil is used, and the outer edge of the case is sandwiched by a sealing bar and heat-sealed to seal the case.

[0003] In the heat sealing process when making a battery, a metal terminal called a tab lead (tablead) is sandwiched between the battery packaging materials and sealed at the same time, so compared with the sealing of a retort bag of food, etc., high temperature, pressure, and long-term heating are required. Therefore, from the viewpoint of heat resistance, polyamide resin is generally used in the resin layer as the outer surface of the shell. However, even if a polyamide resin considered to be highly heat-resistant is used, the small molecular weight compound contained in the resin layer will also precipitate to the surface during sealing, and the packaging material is attached to the sealing strip, causing poor sealing, which is considered a problem.

[0004] In order to prevent poor sealing, polyester resin is laminated or coated on the outside of the polyamide resin layer, but the additional layer sometimes reduces the moldability. In addition, fluororesin is applied to the sealing strip to prevent adhesion, but there are problems such as increased cycle time due to decreased thermal conductivity or the need to increase the sealing temperature.

[0005] As a method for solving the above-mentioned problem, Patent Document 1 discloses a technique for preventing adhesion to a sealing strip by limiting the content of a specific component (caprolactam monomer) contained in a polyamide resin. In addition, Patent Document 2 discloses a technique for preventing adhesion to a sealing strip by regulating the onset temperature derived from the melting heat distribution curve of the polyamide resin.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 6755723

[0009] Patent Document 2: Japanese Patent Application Publication No. 2019-139832 Utility Model Content

[0010] Issues to be Solved by Utility Models

[0011] In recent years, the reduction of cycle time in the manufacture of power storage devices has attracted attention. In order to reduce costs, it is sought to achieve improved productivity by performing heat sealing in a shorter time. In addition, in order to shorten the heat sealing time, there is a tendency to set the sealing temperature and sealing pressure higher. Therefore, in the technologies described in Patent Documents 1 and 2, the problem of poor sealing caused by adhesion to the sealing strip cannot be eliminated.

[0012] Means for solving problems

[0013] In view of the above background technology, an object of the present invention is to provide a battery packaging material that maintains good moldability and can prevent poor sealing due to adhesion to a sealing strip even when heat-sealed at a high temperature.

[0014] That is, the present invention has the configuration described in the following [1] to [7].

[0015] [1] A battery packaging material, characterized in that it is a battery packaging material comprising at least a substrate protection layer, a substrate layer, a barrier layer, and a heat-fusible resin layer in this order from the outside to the inside,

[0016] The substrate protective layer is composed of a resin composition including a resin having a glass transition temperature of 220° C. or higher and a lubricant.

[0017] [2] The battery packaging material according to item 1 above, wherein the resin contained in the substrate protective layer has a glass transition temperature (Tg) of 250°C to 350°C and a number average molecular weight (Mn) of 5,000 to 30,000.

[0018] [3] The battery packaging material according to the above item 2, wherein the resin contained in the substrate protective layer is a polyamide-imide resin containing no curing agent.

[0019] [4] The battery packaging material according to item 3 above, wherein the lubricant contained in the substrate protective layer is at least one lubricant selected from unsaturated fatty acid bisamides and N-substituted amides.

[0020] [5] The battery packaging material according to any one of 1 to 4 above, wherein the amount of resin in the substrate protective layer is 0.1 g / m 2 ~5g / m 2 The content of the lubricant in the aforementioned substrate protective layer is 1 mass % to 20 mass %.

[0021] [6] A molded case characterized in that, in the battery packaging material described in any one of 1 to 5 above, a recessed portion is formed by deep drawing or embossing.

[0022] [7] A battery case characterized by comprising the molded case described in the above item 6.

[0023] Effect of utility model

[0024] In the battery packaging material described in [1] above, the base protective layer is composed of a resin composition containing a resin having a glass transition temperature of 220°C or higher and a lubricant, so the heat resistance is high, and the battery packaging material is prevented from adhering to the sealing strip during heat sealing, and sealing failure is less likely to occur. In addition, the lubricant contained in the base protective layer improves the sliding property and the moldability.

[0025] In the battery packaging material described in [2] above, the glass transition temperature (Tg) of the resin constituting the substrate protective layer is 250°C to 350°C, so the heat resistance is particularly excellent. In addition, the number average molecular weight (Mn) of the resin is 5000 to 30000, and the viscosity of the resin can be easily adjusted with a solvent corresponding to the resin, so that a substrate protective layer of a desired thickness can be formed on the surface of the substrate layer.

[0026] In the battery packaging material described in [3] above, the resin constituting the base protective layer is a polyamide-imide resin containing no curing agent, and therefore has flexibility and is less susceptible to damage such as cracks caused by high temperature and pressure during heat sealing.

[0027] In the battery packaging material described in [4] above, the lubricant added to the substrate protective layer is one or more selected from unsaturated fatty acid bisamides and N-substituted amides. These lubricants have a structure in which an amide group is sandwiched between aliphatic hydrocarbons and are not easily captured by the polyamide-imide resin. Therefore, even if the same amount of addition is used, better sliding properties can be obtained than other lubricants, and moldability can be improved.

[0028] In the battery packaging material described in [5] above, the amount of resin in the substrate protective layer is 0.1 g / m 2 ~5g / m 2 , so the balance between heat resistance and formability is good. In addition, the content of the lubricant in the substrate protective layer is 1% to 20% by mass, so the sliding property is good and the amount of bleeding is suppressed.

[0029] In the molded case described in [6] above, the base protective layer of the battery packaging material contains a lubricant, so deep molding can be performed in deep drawing and embossing, thereby expanding the storage space of the battery body and increasing the battery capacity.

[0030] In the battery case described in [7] above, the base protective layer of the battery packaging material is formed of a resin composition containing a resin having a glass transition temperature of 220° C. or higher, so that adhesion to the sealing strip during heat sealing is prevented, and sealing failure is less likely to occur. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] [ Figure 1 ] is a cross-sectional view showing an example of a battery packaging material of the present invention.

[0032] [ Figure 2 ] Figure 1 A cross-sectional view of a battery case made of a battery packaging material.

[0033] [ Figure 3 ] is a diagram showing the method of the sealing strip adhesion test.

[0034] Description of Reference Numerals

[0035] 1…Battery packaging materials

[0036] 11… Barrier layer

[0037] 12…1st adhesive layer

[0038] 13…Base material layer

[0039] 14…Second adhesive layer

[0040] 15…Thermal fusible resin layer

[0041] 20…Base material protective layer DETAILED DESCRIPTION

[0042] Figure 1 An example of the battery packaging material according to the present invention is shown.

[0043] [Battery Packaging Materials]

[0044] The battery packaging material of the present invention is a laminated body which includes at least a substrate protection layer, a substrate layer, a barrier layer, and a heat-fusible resin layer in this order from the outside to the inside as a basic structure.

[0045] Figure 1 The battery packaging material 1 is a laminated body in which a base layer 13 is bonded to one surface of a barrier layer 11 via a first adhesive layer 12 , a heat-fusible resin layer 15 is bonded to the other surface via a second adhesive layer 14 , and a base protective layer 20 is formed outside the base layer 13 .

[0046] For example Figure 2As shown in FIG. 1 , the battery packaging material 1 is processed into a main body 51 having a recess 52 and a flat cover 55, and the heat-fusible resin layers 15 of the two are arranged to face each other, and the battery main body 56 is accommodated in the recess 52, and the flange 53 around the recess 52 is heat-sealed with the cover 55, thereby manufacturing a battery case 50. In the battery case 50, the base material protection layer 20 is the outside, and the heat-fusible resin layer 15 is the inside. Therefore, in the present invention, when the positions of the layers constituting the battery packaging material are described in terms of directions, the direction of the base material protection layer 20 side is called the outside, and the direction of the heat-fusible resin layer 15 side is called the inside according to the inside and outside directions of the case. In addition, the outermost layer of the battery packaging material 1 is the base material protection layer 20, and the innermost layer is the heat-fusible resin layer 15.

[0047] In the battery packaging material 1 of the present invention, the base protective layer 20 as the outermost layer and the outer surface of the case 50 is formed of a specific resin to which a lubricant is added, thereby maintaining good moldability and preventing sealing defects.

[0048] Hereinafter, each layer constituting the battery packaging material 1 will be described in detail.

[0049] (Base material protective layer)

[0050] The base protective layer 20 is the outermost layer of the battery packaging material 1 and is in contact with the seal bar during heat sealing. The base protective layer 20 is composed of a resin composition containing a resin having a glass transition temperature (Tg) of 220° C. or higher and a lubricant.

[0051] The glass transition temperature (Tg) refers to the temperature at which the molecular chain of the resin particles begins micro-Brownian motion, and is expressed as the starting temperature (starting point) of the heat absorption obtained by differential scanning calorimetry (DSC) analysis based on JISK 7121-1987 "Method for Determining Transition Temperature of Plastics". The higher the glass transition temperature (Tg), the higher the heat resistance. Even if the sealing temperature and / or sealing pressure of the heat seal are increased, it is not easy to adhere to the sealing strip, and poor sealing is not easy to occur. The glass transition temperature (Tg) of the resin used in the present invention is above 220°C, so the heat resistance is high, and the above-mentioned effect is obtained. As resins having a glass transition temperature (Tg) of 220°C or above, polyamide-imide resins (glass transition temperature 250°C-335°C) and polyethersulfone (glass transition temperature 225°C-230°C) can be exemplified.

[0052] Furthermore, since the resin composition contains a lubricant, high moldability can be obtained even when a resin having a high glass transition temperature (Tg) is used.

[0053] Preferred properties of the aforementioned resin are a glass transition temperature (Tg) of 250°C to 350°C and a number average molecular weight (Mn) of 5,000 to 30,000.

[0054] The melting point of the biaxially stretched polyester film used as the material of the substrate layer 13 described later is 250°C, and the melting point of the biaxially stretched polyamide film is 205-210°C. Therefore, by using a resin having a glass transition temperature higher than these melting points, even if heat sealing is performed at a temperature higher than the melting point of the substrate layer 13, adhesion to the sealing strip can be prevented. It should be noted that a resin having a glass transition temperature (Tg) of 350°C or less is easily dissolved in a solvent and has excellent processability, so it is preferred. A particularly preferred glass transition temperature (Tg) is 250°C-300°C.

[0055] The number average molecular weight (Mn) in the present invention is measured based on JIS K 7252-1: 2016 "Plastics - Method for determining the average molecular weight and molecular weight distribution of polymers by size exclusion chromatography Part 1: General". The number average molecular weight (Mn) is determined by the following formula (I) when the number of molecules at molecular weight Mi contained in the polymer is Ni.

[0056] Mn=ΣMiNi / ΣNi…(I)

[0057] If the number average molecular weight (Mn) of the resin is 5000-30000, the viscosity can be easily adjusted by selecting a solvent corresponding to the resin, so that the substrate protection layer 20 of the desired thickness can be formed on the surface of the substrate layer 13. The particularly preferred number average molecular weight (Mn) is 5500-20000. The substrate protection layer 20 can be formed, for example, by adding a lubricant to a resin liquid whose viscosity is adjusted with a solvent and dispersing it, applying the coating liquid thus obtained to the substrate layer 13 with a desired thickness, and drying it at 200°C-300°C. The coating method of the coating liquid can be exemplified by roller coating using a gravure roller, a reverse roller, etc.

[0058] The amount of resin in the substrate protection layer 20 is preferably 0.1 g / m 2 ~5g / m 2 The above-mentioned resin amount is the net amount of resin after removing the lubricant and solvent. The resin amount is 0.1g / m 2 When the heat resistance is improved, the effect of improving the heat resistance is obtained. If the heat resistance is 5 g / m 2 When the resin amount is within the above range, the balance between heat resistance and moldability is good. The most preferred resin amount is 0.2 g / m 2 ~3g / m 2The thickness of the substrate protection layer 20 increases as the amount of the resin increases, and the thickness is preferably 0.1 μm to 6 μm, and particularly preferably 0.3 μm to 2.0 μm.

[0059] As a resin that meets the above-mentioned conditions of glass transition temperature (Tg) and number average molecular weight (Mn), polyamide-imide resin can be cited, and polyamide-imide resin without curing agent can be particularly recommended. Curing agent refers to a substance that promotes the curing of the main material by adding it to the main material. In a two-component curing adhesive or coating, it is an additive that promotes the polymerization reaction of the main agent. The curing reaction does not occur at a 100% reaction rate, and unreacted curing agent remains in the cured adhesive and coating. If unreacted curing agent remains in the substrate protective layer 20, the curing agent adheres to the sealing strip and easily causes poor sealing. Therefore, the substrate protective layer 20 formed by the polyamide-imide resin without curing agent has flexibility and is not prone to damage such as cracks caused by high temperature and pressure during heat sealing.

[0060] The method for forming the substrate protective layer 20 from a polyamide-imide resin without using a curing agent is as follows. The polyamide-imide resin is dissolved in a solvent, the viscosity of the resin liquid is adjusted, and a lubricant is dispersed in the resin liquid to prepare a coating liquid. The coating liquid is applied to the surface of the substrate layer 13 with a desired thickness, and the solvent is volatilized to form a cured film. As the aforementioned dissolving solvent, N-methyl-2-pyrrolidone (NMP), xylene, methyl ethyl ketone, ethanol, toluene, γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, etc. can be used.

[0061] The lubricant is not particularly limited, and unsaturated fatty acid bisamide, N-substituted amide, saturated fatty acid amide, unsaturated fatty acid amide, saturated fatty acid bisamide, etc. can be used. One kind can be used, or two or more kinds can be used in combination. These lubricants are precipitated on the surface of the base protective layer 20, provide sliding properties to the outer surface of the battery packaging material 1, and improve the moldability of the battery packaging material 1.

[0062] Examples of the unsaturated fatty acid amide include ethylenebisoleic acid amide, ethylenebiserucic acid amide, hexamethylenebisoleic acid amide, N,N′-dioleyl adipamide, and N,N′-dioleyl sebacic acid amide.

[0063] Examples of the N-substituted amides include N-oleyl palmitamide (NOPA), N-stearyl stearamide (NSSA), N-stearyl oleamide (NSOA), N-oleyl stearamide (NOSA), and N-stearyl erucamide (NSEA).

[0064] Examples of the saturated fatty acid amide include lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, and hydroxystearic acid amide.

[0065] Examples of the saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, and N,N'-distearyl sebacic acid amide.

[0066] Among the above lubricants, at least one lubricant selected from unsaturated fatty acid bisamides and N-substituted amides is recommended. These lubricants have a structure in which the amide group is sandwiched by aliphatic hydrocarbons and are not easily captured by the polyamide-imide resin. Therefore, even if the same addition amount is used, better sliding properties can be obtained than other lubricants, and moldability can be improved.

[0067] The content of the lubricant, i.e., the ratio of the lubricant to the total amount of the resin and the lubricant, is preferably in the range of 1% to 20% by mass. When the content of the lubricant is 1% by mass or more, good sliding properties are obtained, and when it is 20% by mass or less, the amount of oozing out does not become excessive, and there is no concern that the lubricant precipitates in the form of white powder on the surface of the base protective layer 20 and adheres to the molding die or the manufacturing line. The content of the lubricant is particularly preferably 2% to 10% by mass.

[0068] (Base material layer)

[0069] The aforementioned base material layer 13 uses a heat-resistant resin film that does not melt at the heat-sealing temperature when the battery packaging material 1 is heat-sealed. As the aforementioned heat-resistant resin, a heat-resistant resin having a melting point that is 10°C or higher, preferably 20°C or higher, than the melting point of the resin constituting the heat-fusible resin layer 15 is used. As a resin that meets this condition, for example, polyamide films such as nylon films, polyester films, etc. can be cited, and their stretched films are preferably used. Among them, as the aforementioned base material layer 13, it is particularly preferred to use biaxially stretched polyamide films such as biaxially stretched nylon films, biaxially stretched polybutylene terephthalate (PBT) films, biaxially stretched polyethylene terephthalate (PET) films, or biaxially stretched polyethylene naphthalate (PEN) films. As the aforementioned nylon film, there is no particular limitation, for example, nylon 6 film, nylon 6,6 film, MXD nylon film, etc. can be cited. The base material layer 13 may be formed as a single layer, or may be formed as a multilayer including, for example, a polyester film / polyamide film (a multilayer including a PET film / nylon film, etc.).

[0070] The thickness of the substrate layer 13 is preferably 9 μm to 50 μm, which can ensure sufficient strength as a packaging material, and can reduce the stress during forming such as bulging and drawing, and can improve the formability. The thickness of the substrate layer 13 is further preferably 12 μm to 30 μm. In the case of multiple layers of the substrate layer 13, the total thickness is taken as the above thickness. In addition, the thickness of the adhesive that bonds the multiple layers is also included in the above thickness.

[0071] (Barrier layer)

[0072] The barrier layer 11 is responsible for imparting gas barrier properties to the battery packaging material 1 to prevent the intrusion of oxygen and moisture. The barrier layer 11 may be any metal foil without particular limitation, and examples thereof include aluminum foil, SUS foil (stainless steel foil), copper foil, nickel foil, titanium foil, and clad foil, and aluminum foil is preferably used. The thickness of the barrier layer 11 is preferably 20 μm to 100 μm. By being 20 μm or more, pinholes can be prevented from being generated during rolling when manufacturing the metal foil, and by being 100 μm or less, stress during forming such as embossing and drawing can be reduced, thereby improving formability. The particularly preferred thickness of the barrier layer 11 is 30 μm to 80 μm.

[0073] In addition, as for the barrier layer 11, it is preferred that a chemical conversion film is formed by subjecting at least the surface of the metal foil on the side of the heat-fusible resin layer 15 to a base treatment such as a chemical conversion treatment. The chemical conversion film can improve the corrosion resistance of the metal foil surface and prevent the contents of the battery such as the electrolyte from corroding the metal foil. The chemical conversion film can be formed, for example, by subjecting the metal foil to a chromate treatment or a non-chromium chemical conversion treatment using a zirconium compound.

[0074] In the chromate treatment method, for example, an aqueous solution of any one of the following mixtures 1) to 3) is applied to the surface of the degreased metal foil and then dried.

[0075] 1) A mixture of phosphoric acid, chromic acid, and at least one of a metal salt of fluoride and a non-metal salt of fluoride

[0076] 2) A mixture of phosphoric acid, any one of an acrylic resin, a chitosan derivative resin and a phenolic resin, and at least one of chromic acid and a chromium (III) salt

[0077] 3) A mixture of phosphoric acid, any one of an acrylic resin, a chitosan derivative resin, and a phenolic resin, at least one of chromic acid and a chromium (III) salt, and at least one of a metal salt of a fluoride and a non-metal salt of a fluoride

[0078] The amount of chromium deposited on the chemical conversion film is preferably 0.1 mg / m 2 ~50 mg / m 2 , especially preferably 2 mg / m 2 ~20 mg / m 2 The chemical conversion film having such an amount of chromium deposited thereon can provide a battery packaging material having high corrosion resistance.

[0079] (Thermal Fusible Resin Layer)

[0080] The heat-fusible resin layer 15 has excellent chemical resistance even against highly corrosive electrolytes and the like, and also plays a role in imparting heat-sealing properties to the battery packaging material 1 .

[0081] The resin constituting the aforementioned heat-fusible resin layer 15 is preferably a polyolefin resin, and polyethylene resin or polypropylene resin can be exemplified, and propylene resin is particularly preferred. As the propylene resin, unstretched films such as cast polypropylene (CPP) and blown polypropylene (IPP) are preferred. As the aforementioned propylene resin, in addition to a homopolymer of propylene (hPP), an ethylene-propylene copolymer containing ethylene and propylene as copolymer components can also be exemplified. The aforementioned ethylene-propylene copolymer can be any of a random copolymer (rPP) and a block copolymer (bPP).

[0082] In addition, the heat-fusible resin layer may be a single layer or multiple layers, and a multilayer film constituting the multiple layers of the heat-fusible resin layer may be produced by coextrusion, etc. From the perspective of excellent heat sealability, delamination resistance, and insulation, among the various propylene resin films mentioned above, a three-layer coextruded CPP film having hPP or bPP as an intermediate layer and rPP layers arranged on both sides of the intermediate layer is recommended.

[0083] The thickness of the heat-fusible resin layer 15 is preferably 20 μm to 100 μm, and particularly preferably 30 μm to 80 μm. The total thickness of the multilayer film is also preferably in the above range. As for the preferred thickness ratio of each layer of the three-layer film, when the total thickness is set to 10, the layer on the side of the second adhesive layer 14: the middle layer: the innermost layer = 1-3: 4-8: 1-3.

[0084] In order to improve the sliding property of the battery packaging material 1, a fatty acid amide-based lubricant may be added to the heat-fusible resin layer 15. The lubricant content in the heat-fusible resin layer 15 is preferably 500 to 4000 ppm by mass.

[0085] (First Adhesive Layer)

[0086] The first adhesive layer 12 is not particularly limited, and for example, a two-component curing type polyurethane adhesive, acrylic adhesive, polyacrylate adhesive, modified polypropylene adhesive, polyester adhesive, polyamide adhesive, or epoxy adhesive can be used. As the two-component curing type adhesive, for example, a two-component curing type adhesive composed of the following first liquid (main agent) and the following second liquid (curing agent) can be cited, wherein the first liquid (main agent) is formed by one or more polyols selected from the group consisting of polyurethane polyols, polyester polyols, polyether polyols, and polyesterurethane polyols, and the second liquid (curing agent) is formed by isocyanate. Among them, it is preferred to use a two-liquid curing adhesive composed of the following first liquid and the following second liquid (curing agent), wherein the first liquid is formed by one or more polyols selected from the group consisting of polyester polyols and polyester urethane polyols, and the second liquid (curing agent) is formed by isocyanate. The preferred thickness of the first adhesive layer 12 is 2 μm-5 μm.

[0087] (Second Adhesive Layer)

[0088] The second adhesive layer 14 is not particularly limited, and may be, in addition to the same adhesive as the first adhesive layer 12, polyolefin resins such as polyolefin, carboxylic acid-modified polyolefin, and metal-modified polyolefin, polyvinyl acetate resin, (meth) acrylic resin, and amino resin. These adhesive resins may be used alone or in combination of two or more.

[0089] When the above-mentioned adhesive (the adhesive exemplified in the first adhesive layer) is used, the adhesive composition is applied to the barrier layer 11 or the heat-fusible resin layer 15 by gravure coating, reverse roll coating, etc., and the solvent is evaporated to form a dry film, and then the barrier layer 11 and the heat-fusible resin layer 15 are bonded. Then, the adhesive composition is cured according to the curing conditions. The barrier layer 11 and the base material layer 13 bonded by the above-mentioned first adhesive layer 12 can also be bonded by the same method.

[0090] In addition, when the aforementioned adhesive resin is used, the barrier layer 11, the second adhesive layer 14, and the thermally fusible resin layer 15 are laminated by the following methods, etc.: a method of laminating by co-extruded the adhesive resin and the resin forming the thermally fusible resin layer 15 onto the barrier layer 11 (extrusion lamination method); a method of pre-forming a laminated body obtained by laminating the adhesive resin and the thermally fusible resin layer 15, and laminating the laminated body onto the barrier layer 11 by a thermal lamination method; a method of laminating the barrier layer 11 and the thermally fusible resin layer 15 while flowing molten adhesive resin between them (sandwich lamination method).

[0091] [Molding case and battery case]

[0092] The molded case of the utility model has a recessed portion formed by deep drawing or embossing the above-mentioned battery packaging material. Figure 2 The main body 51 with the recess 52 belongs to the molded shell of the utility model.

[0093] A battery case of the present invention includes the molded case described above. Figure 2 The battery case 50 including the main body 51 belongs to the battery case of the present invention.

[0094] In the battery packaging material of the present invention, the substrate protective layer has good sliding properties and excellent formability, which is advantageous for the formation of the recess 52 and is suitable for the formation of deep recesses. In addition, by forming a deep recess, the storage space of the battery body is expanded, thereby increasing the battery capacity. In addition, in the battery case of the present invention, the substrate protective layer of the battery packaging material is formed of a resin composition containing a resin with a glass transition temperature of 220°C or more, so it is prevented from adhering to the sealing strip during heat sealing, and poor sealing is not likely to occur.

[0095] Example

[0096] As Examples 1-8 and Comparative Examples 1-3, Figure 1 The battery packaging materials 1 are in a laminated form. These battery packaging materials 1 are common in that a base protective layer 20, a base layer 13, a first adhesive layer 12, a barrier layer 11, a second adhesive layer 14, and a heat-fusible resin layer 15 are laminated in order from the outside to the inside, but the resins and lubricants constituting the base protective layer 20 are different (see Table 1). In addition, Comparative Example 4 is a laminate of a base layer 13, a first adhesive layer 12, a barrier layer 11, a second adhesive layer 14, and a heat-fusible resin layer 15, and is a battery packaging material without a base protective layer (not shown).

[0097] The materials common to the battery packaging materials of the respective examples are as follows.

[0098] (Common Materials)

[0099] As the barrier layer 11, an aluminum foil made of A8021-O specified in JIS H4160 and having a thickness of 35 μm was used. A chemical conversion treatment solution containing phosphoric acid, polyacrylic acid (acrylic resin), chromium (III) salt compound, water, and alcohol was applied to both sides of the aluminum foil, and then dried at 180° C. to form a chemical conversion film, and the obtained product was used. The chromium adhesion amount of the chemical conversion film was 10 mg / m per single side. 2 .

[0100] A biaxially stretched nylon 6 film having a thickness of 15 μm was used as the base material layer 13. One surface of the biaxially stretched nylon 6 film was subjected to a corona treatment.

[0101] As the heat-adhesive resin layer 15 , a cast polypropylene (CPP) film having a thickness of 30 μm was used.

[0102] As the first adhesive layer 12 , a two-component curable urethane adhesive is used.

[0103] As the second adhesive layer 14, a two-component curable maleic acid-modified acrylic adhesive was used.

[0104] (Examples 1 and 2)

[0105] A first adhesive layer 12 having a thickness of 3 μm was formed on one surface of the barrier layer 11 having the chemical conversion film formed thereon, and dry-laminated on the corona-treated surface of the base layer 13. The layer was then aged at 60° C. for 7 days to produce a first intermediate laminate.

[0106] The coating liquid for forming the base protective layer 20 was prepared using the following materials.

[0107] A polyamide-imide resin having a glass transition temperature (Tg) and a number average molecular weight (Mn) shown in Table 1 was dissolved in a mixed solvent of ethanol:toluene = 1:1 (mass ratio) to prepare a resin liquid having a polyamide-imide resin solid content concentration of 25 mass %, and the lubricant shown in Table 1 was added to the resin liquid and dispersed to prepare a coating liquid. The amount of the lubricant added was adjusted so that the lubricant amount relative to the total amount of the resin and the lubricant was at the ratio shown in Table 1.

[0108] The prepared coating liquid was applied to the surface of the substrate layer 13 of the first intermediate laminate using a gravure roll and dried at 100° C. for 10 seconds to form a substrate protective layer 20. This laminate was used as the second intermediate laminate. The resin amount and lubricant content in the substrate protective layer 20 are shown in Table 1.

[0109] Next, a second adhesive layer 14 with a thickness of 2 μm was formed on the other side of the barrier layer 11 of the second intermediate laminate, and a heat-fusible resin layer 15 was laminated, and the laminate was sandwiched between a rubber roller and a laminating roller heated to 100° C. for pressure bonding, thereby performing dry lamination to produce a laminate, which was then wound on a roll. The laminate wound on the roll was aged at 40° C. for 7 days to obtain a battery packaging material 1. The thickness of the substrate protective layer 20 after aging is shown in Table 1.

[0110] (Examples 3 and 4)

[0111] The coating liquid for forming the base protective layer 20 was prepared using the following materials.

[0112] A polyamide-imide resin having a glass transition temperature (Tg) and a number average molecular weight (Mn) shown in Table 1 was dissolved in a mixed solvent of N-methyl-2-pyrrolidone:xylene:methyl ethyl ketone = 3.5:2.5:1 (mass ratio) to prepare a resin liquid having a polyamide-imide resin solid content concentration of 30% by mass, and a lubricant shown in Table 1 was added to the resin liquid and dispersed to prepare a coating liquid. The amount of the lubricant added was adjusted so that the lubricant amount relative to the total amount of the resin and the lubricant was at the ratio shown in Table 1.

[0113] The prepared coating liquid was applied to the surface of the substrate layer 13 of the first intermediate laminate as in Example 1 using a gravure roll and dried at 190° C. for 30 seconds to form a substrate protective layer 20. This laminate was used as the second intermediate laminate. The amount of resin in the substrate protective layer 20 is shown in Table 1.

[0114] Next, the thermally fusible resin layer 15 was laminated on the second intermediate laminate in the same manner as in Example 1 and aged to obtain a battery packaging material 1 .

[0115] (Example 5)

[0116] The coating liquid for forming the base protective layer 20 was prepared using the following materials.

[0117] A polyamide-imide resin having a glass transition temperature (Tg) and a number average molecular weight (Mn) shown in Table 1 was dissolved in an N-methyl-2-pyrrolidone solvent to prepare a resin solution having a polyamide-imide resin solid content concentration of 15% by mass, and a lubricant shown in Table 1 was added to the resin solution and dispersed to prepare a coating solution. The amount of the lubricant added was adjusted so that the lubricant amount relative to the total amount of the resin and the lubricant was at the ratio shown in Table 1.

[0118] The prepared coating liquid was applied to the surface of the substrate layer 13 of the first intermediate laminate as in Example 1 using a gravure roll and dried at 190° C. for 30 seconds to form a substrate protective layer 20. This laminate was used as the second intermediate laminate. The amount of resin in the substrate protective layer 20 is shown in Table 1.

[0119] Next, the thermally fusible resin layer 15 was laminated on the second intermediate laminate in the same manner as in Example 1 and aged to obtain a battery packaging material 1 .

[0120] (Example 6)

[0121] The coating liquid for forming the base protective layer 20 was prepared using the following materials.

[0122] A polyamide-imide resin having a glass transition temperature (Tg) and a number average molecular weight (Mn) shown in Table 1 was dissolved in a mixed solvent of γ-butyrolactone:1,3-dimethyl-2-imidazolidinone=32:1 (mass ratio) to prepare a resin liquid having a polyamide-imide resin solid content concentration of 20 mass %, and a lubricant shown in Table 1 was added to the resin liquid and dispersed to prepare a coating liquid. The amount of the lubricant added was adjusted so that the lubricant amount relative to the total amount of the resin and the lubricant was at the ratio shown in Table 1.

[0123] The prepared coating liquid was applied to the surface of the substrate layer 13 of the first intermediate laminate as in Example 1 using a gravure roll and dried at 180° C. for 30 seconds to form a substrate protective layer 20. This laminate was used as the second intermediate laminate. The amount of resin in the substrate protective layer 20 is shown in Table 1.

[0124] Next, the thermally fusible resin layer 15 was laminated on the second intermediate laminate in the same manner as in Example 1 and aged to obtain a battery packaging material 1 .

[0125] (Example 7)

[0126] The coating liquid for forming the base protective layer 20 was prepared using the following materials.

[0127] A polyamide-imide resin having a glass transition temperature (Tg) and a number average molecular weight (Mn) shown in Table 1 was dissolved in an N-methyl-2-pyrrolidone solvent to prepare a resin solution having a polyamide-imide resin solid content concentration of 14% by mass, and a lubricant shown in Table 1 was added to the resin solution and dispersed to prepare a coating solution. The amount of the lubricant added was adjusted so that the lubricant amount relative to the total amount of the resin and the lubricant was at the ratio shown in Table 1.

[0128] The prepared coating liquid was applied to the surface of the substrate layer 13 of the first intermediate laminate as in Example 1 using a gravure roll and dried at 190° C. for 30 seconds to form a substrate protective layer 20. This laminate was used as the second intermediate laminate. The amount of resin in the substrate protective layer 20 is shown in Table 1.

[0129] Next, the thermally fusible resin layer 15 was laminated on the second intermediate laminate in the same manner as in Example 1 and aged to obtain a battery packaging material 1 .

[0130] (Example 8)

[0131] The coating liquid for forming the base protective layer 20 was prepared using the following materials.

[0132] A polyethersulfone resin having a glass transition temperature (Tg) and a number average molecular weight (Mn) shown in Table 1 was dissolved in an N-methyl-2-pyrrolidone solvent to prepare a resin solution having a polyethersulfone resin solid content concentration of 10% by mass, and the lubricant shown in Table 1 was added to the resin solution and dispersed to prepare a coating solution. The amount of the lubricant added was adjusted so that the amount of the lubricant relative to the total amount of the resin and the lubricant was the ratio shown in Table 1.

[0133] The prepared coating liquid was applied to the surface of the substrate layer 13 of the first intermediate laminate as in Example 1 using a gravure roll and dried at 190° C. for 30 seconds to form a substrate protective layer 20. This laminate was used as the second intermediate laminate. The amount of resin in the substrate protective layer 20 is shown in Table 1.

[0134] Next, the thermally fusible resin layer 15 was laminated on the second intermediate layer stack in the same manner as in Example 1 and aged to obtain a battery packaging material 1 .

[0135] (Comparative Example 1)

[0136] A battery packaging material 1 was prepared in the same manner as in Example 7 except that no lubricant was added to the coating solution for forming the substrate protective layer 20 .

[0137] (Comparative Example 2)

[0138] The coating liquid for forming the base protective layer 20 was prepared using the following materials.

[0139] A polymethacrylic acid resin having a glass transition temperature (Tg) and a number average molecular weight (Mn) shown in Table 1 was dissolved in a mixed solvent of N-methyl-2-pyrrolidone:xylene:methyl ethyl ketone = 3.5:2.5:1 (mass ratio) to prepare a resin liquid having a polymethacrylic acid resin solid content concentration of 10 mass %, and the lubricant shown in Table 1 was added to the resin liquid and dispersed to prepare a coating liquid. The amount of the lubricant added was adjusted so that the lubricant amount relative to the total amount of the resin and the lubricant was the ratio shown in Table 1.

[0140] The prepared coating liquid was applied to the surface of the substrate layer 13 of the first intermediate laminate as in Example 1 using a gravure roll and dried at 190° C. for 30 seconds to form a substrate protective layer 20. This laminate was used as the second intermediate laminate. The amount of resin in the substrate protective layer 20 is shown in Table 1.

[0141] Next, the thermally fusible resin layer 15 was laminated on the second intermediate laminate in the same manner as in Example 1 and aged to obtain a battery packaging material 1 .

[0142] (Comparative Example 3)

[0143] The coating liquid for forming the base protective layer 20 was prepared using the following materials.

[0144] A polyester urethane resin having a glass transition temperature (Tg) and a number average molecular weight (Mn) shown in Table 1 was dissolved in a mixed solvent of methyl ethyl ketone: toluene = 2:1 (mass ratio) to prepare a resin liquid having a polyester urethane resin solid content concentration of 40% by mass, and the lubricant shown in Table 1 was added to the resin liquid and dispersed to prepare a coating liquid. The amount of the lubricant added was adjusted so that the lubricant amount relative to the total amount of the resin and the lubricant was the ratio shown in Table 1.

[0145] The prepared coating liquid was applied to the surface of the substrate layer 13 of the first intermediate laminate similar to Example 1 using a gravure roll and dried at 100° C. for 10 seconds to form a substrate protective layer 20. This laminate was used as the second intermediate laminate. The amount of resin in the substrate protective layer 20 is shown in Table 1.

[0146] Next, the thermally fusible resin layer 15 was laminated on the second intermediate laminate in the same manner as in Example 1 and aged to obtain a battery packaging material 1 .

[0147] (Comparative Example 4)

[0148] A second adhesive layer 14 having a thickness of 2 μm was formed on the other side of the barrier layer 11 of the first intermediate laminate similar to Example 1, and a heat-fusible resin layer 15 was laminated thereon, and the laminate was pressed and bonded between a rubber roller and a laminating roller heated to 100° C., thereby performing dry lamination to produce a laminate, which was then wound around a roll. The laminate wound around a roll was aged at 40° C. for 7 days to prepare a battery packaging material.

[0149] [Evaluation of battery packaging materials]

[0150] The adhesion easiness and moldability of the produced battery packaging material 1 to the sealing strip were evaluated by the following method. The evaluation results are shown in Table 1.

[0151] (Ease of attachment to weather strip: Weather strip attachment test)

[0152] Figure 3 An outline of the method of the weather strip adhesion test is shown.

[0153] A rectangular sample of 50 mm in width and 100 mm in length was collected from each battery packaging material 1, and the sample was folded in half at the center of the long side with the base protective layer 20 of the sample on the outside and the heat-fusible resin layer 15 on the inside to prepare a 50 mm × 50 mm wide bending test piece 31. At one end 32 of the bending test piece 31, the two short sides of the rectangular sample were aligned and overlapped, and a loop was formed at the other end 33. Then, a stranded wire 37 was passed through the other end 33 to form a loop.

[0154] One end 32 of the bending test piece 31 was clamped between an upper aluminum mold 35 with a sealing width of 5 mm and a lower aluminum mold 36 coated with fluororesin with a sealing width of 5 mm, and both the upper mold 35 and the lower mold 36 were heated to perform heat sealing. The heat sealing was performed under two temperature conditions: 210°C × 0.3 MPa × 3 seconds and 230°C × 0.3 MPa × 3 seconds.

[0155] After heat sealing, the lower die 36 is separated from the bending test piece 31, and the bending test piece 31 is attached to the upper die 35. Then, the hook of the push-pull force gauge (model DPX-10: manufactured by IMADA) is hung on the loop of the strand 37 at the other end 33 of the bending test piece 31, and the bending test piece 31 is pulled until it is separated from the upper die 35. The tensile strength at the time of separation is measured and is taken as the adhesion strength. The measured tensile strength (adhesion strength) is evaluated according to the following four levels of the standard, and ABC is regarded as passing.

[0156] A: Tensile strength is less than 0.1kgf

[0157] B: Tensile strength is 0.1kgf or more and less than 0.8kgf

[0158] C: Tensile strength is 0.8kgf or more and less than 1.0kgf

[0159] D: Tensile strength is 1.0kgf or more

[0160] (Moldability)

[0161] The prepared battery packaging material 1 was cut into 100 mm × 125 mm pieces as a raw material for molding. Then, a punch (punch shape: 33 mm × 54 mm, corner R: 2 mm, punch shoulder R: 1.3 mm) and a die (die shape: die shoulder R: 1 mm) were used to perform deep drawing using a press (model: TP-25C-XZ) manufactured by Amada Co., Ltd. The deep drawing was performed in such a way that the top surface of the punch was in contact with the heat-fusible resin layer 15 of the raw material for molding and the base material protective layer 20 protruded outward, and the molding depth D was changed in units of 0.5 mm.

[0162] Then, the corners of the molded product were illuminated and the presence of transmitted light caused by pinholes and cracks was visually observed. The maximum molding depth (mm) at which good molding without any pinholes or cracks was possible was investigated. For the maximum molding depth, the moldability was evaluated based on the following judgment criteria, and ABC was considered acceptable.

[0163] A: Maximum forming depth is more than 6mm

[0164] B: Maximum forming depth is 5mm or more and less than 6mm

[0165] C: Maximum forming depth is 4 mm or more and less than 5 mm

[0166] D: Maximum forming depth is less than 4mm

[0167] [Table 1]

[0168]

[0169] It was confirmed from Table 1 that the battery packaging material of the example was less likely to adhere to the seal bar during heat sealing and had good moldability.

[0170] Industrial Applicability

[0171] The battery packaging material of the present invention can be suitably used as a casing material for electrical storage devices such as batteries and capacitors.

[0172] This application claims the priority of Japanese patent application No. 2022-203602 filed on December 20, 2022, the disclosure of which directly constitutes a part of this application.

[0173] The terms and expressions used herein are for explanation rather than limitation, and do not exclude any equivalents of the features disclosed and described herein, and should be understood to allow various modifications within the scope of the invention claimed.

Claims

1. A battery packaging material, characterized in that: The battery packaging material comprises at least a substrate protective layer, a substrate layer, a barrier layer, and a heat-fusible resin layer in this order from the outside to the inside. The substrate protection layer is composed of a polyamide-imide resin to which a lubricant is added.

2. A molded shell, characterized in that: The molded case is formed by forming a recessed portion obtained by deep drawing or embossing in the battery packaging material according to claim 1 .

3. A battery housing, characterized in that: A molded case according to claim 2 is provided.

Citation Information

Patent Citations

  • Jacket material for power storage device and power storage device

    JP2019139832A